Efeitos de um protocolo de treinamento em circuito periodizado via telerreabilitação para adultos com osteoartrite de joelho - Aily, Jéssica Bianca (Universidade Federal de São Carlos, 2023)
Objectives: To investigate whether a periodized circuit training protocol delivered via telerehabilitation is as effective as the same exercise protocol applied face-to-face on self-reported pain and physical function, as well as the clinical and morphological characteristics of adults with knee OA. Secondarily, the objective was to determine the concurrent validity and reliability of performance-based tests recommended by the International Society for Osteoarthritis Research (OARSI) applied remotely in the same population. Three studies were performed: I: Effects of a periodized circuit training protocol delivered via telerehabilitation compared with the face-to-face method for adults with knee osteoarthritis: protocol for a randomized controlled non-inferiority trial; II: Telerehabilitation is non-inferior to face-to-face care to deliver a periodized circuit training protocol for knee osteoarthritis: a randomized controlled non-inferiority trial; III: Concurrent validity and reliability of telehealth performance-based tests in adults with knee osteoarthritis. Methods: One hundred participants with knee OA grades II and III, aged 40 years or older and BMI<30kg/m2 were randomized into two groups: the control group, face-to-face (FtF), (n = 50; mean age = 54.8; women 60%) received the face-to-face circuit training protocol. The intervention group, telerehabilitation (TR), (n = 50; mean age = 53.1; women 60%) received the circuit training protocol through distance telerehabilitation directly through video recordings; and were followed by periodized phone calls to motivate and educate participants. Primary outcomes were pain intensity (visual analogue scale; VAS) and disability (Western Ontario and McMaster Universities Osteoarthritis Index – WOMAC physical function subscale) measured at 14 weeks and 26 weeks after baseline assessments. Secondary outcomes included objective physical function, strength, pain catastrophizing, and morphological measures (muscle architecture; body and thigh composition). In study III, a secondary analysis of studies I and II, thirty-two participants were submitted to performance-based test evaluation by two approaches, telehealth and face-to-face, on the same day. All telehealth assessments were conducted and recorded using the Microsoft Teams Software (version: 1.3.00.4460) for later analysis of concurrent validity and inter- and intra-rater reliabilities. Results: Results from Study II showed that no between-group differences were detected on the VAS and WOMAC physical function subscale at the primary endpoint of 14 weeks (p > 0.05). Clinical (quadriceps muscle strength, physical function and pain catastrophizing) and morphological (body and thigh composition, muscle architecture) outcomes also did not differ between groups. Study III showed a high degree of concurrent validity for all performance-based tests, as well as excellent inter- and intra-rater agreement. Conclusion: Adults with knee OA submitted to a periodized circuit training protocol for telerehabilitation achieve physical and functionally non-inferior to participants receiving the same face-to-face rehabilitation program. In the same sense, the remote assessment of performance-based tests is a valid and reliable tool to measure the physical function of adults with knee OA using the Microsoft Teams Software.
Effects of a periodized circuit training protocol delivered via telerehabilitation for adults with knee osteoarthritis
Keywords: Fisioterapia; Osteoartrite de joelho; Dor; Função física; Telerreabilitação; Physiotherapy; Knee osteoarthritis; Pain; Physical function; Telerehabilitation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL